Angiosarcoma of the scalp successfully treated with Nivolumab-A case report - Casandra A. Coltoiu; Marie Piroth; Julia Bonnelye; Ute Zimmermann; Gaëlle Quereux (Wiley, 2024)
Abstract Angiosarcomas are rare, aggressive tumours with a propensity for the head and neck region. Surgery is the mainstay of treatment of localised angiosarcoma, but in unresectable or metastatic disease, the treatment is much more challenging. Traditionally, chemotherapy (Paclitaxel in particular) has been the treatment of choice. Evidence from case reports and small trials shows that PD1 inhibitors have activity against angiosarcomas, despite the lack of a large clinical trial data demonstrating definitive efficacy. The present case exemplifies the susceptibility of this malignancy to anti‐PD1 agents. We report a 77‐year‐old male patient with an advanced, multifocal angiosarcoma of the frontotemporal and malar region. The patient was pretreated using the association of Propranolol and Endoxan and then Paclitaxel. Because of the lack of efficacy, the patient was started on Nivolumab as the third line of therapy. After five cycles of immunotherapy, an excellent response was achieved, with complete remission of the cutaneous lesions as well as a partial remission of the hepatic nodules. The duration of response is currently 14 months, the patient being still alive at the present time. This case suggests that immune checkpoint inhibitors may represent a viable therapeutic option that needs further exploration for the treatment of locally advanced, unresectable or metastatic cases of cutaneous angiosarcoma.